Misconception Analysis of Acid-Base Material in SMK Kimia PGRI Serang City - Febriyanti, Beta; Sari, Sandi Danar Cynthia; Fajriyah, Laelatul; Sa’diah, Siti; Mulamawarni, Ken Hastu; Merlina, Pina (LAVOISIER: Chemistry Education Journal, 2024)
Chemistry is a branch of science that studies various natural phenomena, including the properties, changes in matter, structure, and the energy that accompanies them. The study of chemistry is interconnected with its concepts, making it continuous. The aim of this research is to analyze misconceptions about acid-base materials using a four-tier multiple-choice diagnostic test instrument. The research method used is descriptive qualitative, aiming to analyze student misconceptions. The subjects of this research were class XI students of SMK KIMIA PGRI SERANG CITY. To collect data, observation techniques, four-tier diagnostic tests, interviews, and documentation were used. The results of this research show that 40% of students have misconceptions about acid-base materials, 13% of students understand the concept, and 47% of students don't understand the concept. More students experience misconceptions compared to students who understand the concept. Based on the percentage results, the level of misconceptions for class XI students at SMK KIMIA PGRI Serang City is classified as medium. According to the results of interviews with students, student misconceptions are caused by two factors: internal factors (coming from students) and external factors (coming from learning media such as books and teachers). The factor that causes students' misconceptions is that schools emphasize practice rather than theory, where practice is 60% and theory is 40%.